2018
DOI: 10.1177/1358863x18767761
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and comorbidities in patients with hereditary hemorrhagic telangiectasia

Abstract: There are only a few published studies that demonstrate associations between life expectancy, severe comorbidities, and their complications in patients with hereditary hemorrhagic telangiectasia (HHT). Relatives of 73 deceased patients with suspected HHT completed a questionnaire about causes of death, and symptoms and comorbidities that the patients had developed. We compared the data for 55 cases where HHT had been clinically confirmed with the general population. Patients suffering from HHT lost, on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
22
0
4
Order By: Relevance
“…In the past, HHT patients presented with major complications especially from undiagnosed PAVMs such as hemothorax and paradoxical emboli leading to ischemic stroke or cerebral abscess [6,8]. These complications significantly reduced the quality of life and the life expectancy [9][10][11]. Several studies have shown a decreased life expectancy in HHT patients that did not receive a systematic HHT screening and treatment [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, HHT patients presented with major complications especially from undiagnosed PAVMs such as hemothorax and paradoxical emboli leading to ischemic stroke or cerebral abscess [6,8]. These complications significantly reduced the quality of life and the life expectancy [9][10][11]. Several studies have shown a decreased life expectancy in HHT patients that did not receive a systematic HHT screening and treatment [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…More cases of HHT and pulmonary hypertension were reported among patients with ACVRL1 mutations than among patients with ENG mutations (5). Previous studies, that did not include genetic information about ACVRL1 mutations, found that HHT and pulmonary hypertension patients had a higher mortality, and died due to cardiac diseases associated with pulmonary hypertension, sepsis, and major bleeding related to HHT (6,14,15). The prognostic information in Table 3, which describes the reported cases of HHT and pulmonary hypertension in patients with ACVRL1 mutations, indicates that patients died due to right heart failure, sepsis, bleeding, and rupture of arteriovenous malformation after 1.8 to 21 years' follow-up (16-22).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HHT are reported to have lower life expectancy than the general population (6)(7)(8). There are no differences regarding the survival rate between HHT patients with ACVRL1 mutations and those with ENG mutations (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary hemorrhagic telangiectasia (HHT) is a genetic disorder, leading to vascular abnormalities with potentially serious clinical implications [1,2]. It is an autosomal dominant disease with an estimated prevalence of 1:6.500 in Denmark [3].…”
Section: Introductionmentioning
confidence: 99%